(untitled) (Significação: Journal of Audiovisual Culture, 2011)
This paper analyzes two Brazilian movies, Rio, zona Norte (Nelson Pereira dos Santos, 1957) and Orfeu (Carlos Diegues, 1999), focusing on the way these works portray Afro-descendant people. It must be considered that both movies have black people as their main characters, and the cast is also composed of Afro-Brazilian actors and actresses; in addition, these films take the lives of popular composers who live in the Rio de Janeiro’s “favelas” as one of their themes. However, Rio, zona Norte’s theme is the life of musical creators not incorporated by the Brazilian cultural industry, which was still in the golden phase of radio period; Orfeu’s plot, nonetheless, addresses an artist who has relationships with the big media right in the middle of the television corporation’s era.